Implementasi Pengadaan Barang Dan Jasa Di Balai Konservasi Sumber Daya Alam Provinsi NTB - Dony Ramdhani Subagdja; Diangsa Wagian (Private Law, 2022)
This research has the purpose to find out how The implementation of the procurement of goods and services between the Natural Resources Conservation Center of the Province of NTB with CV. Multi Indo Perkasa, and find out the obstacle factors in the procurement of goods and services in the Natural Resources Conservation Center of the Province of NTB. This research uses a normative legal research and an empirical legal research method. Based on this research, the implementation of the procurement of goods and services at the Natural Resources Conservation Center of the Province of NTB with CV Multi Indo Perkasa is according to The President Regulation Number 16 of 2018 concerning the government procurement of goods and services, The obstacle factors in the procurement of goods and services at the Natural Resources Conservation Center of the Province of NTB are about human resources, because several of the office staff do not have procurement of goods and services expert certificates, and they are difficult to qualify or determining the specifications of goods and reasonable prices without mentioning the brand, this is occurred because they are not allowed to refer to a certain brand or product.